Meningkatkan Hasil Belajar Geografi Siswa di Kelas X IPS 3 MAN 1 Kendari dengan Menerapkan Model Pembelajaran Probing Prompting pada Bahan Utama Dinamika Atmosfer dan Dampaknya pada Kehidupan - Putriani Putriani; La Ode Amaluddin (UNM Geographic Journal, 2019)
MAN 1 Kendari is one of the schools in Kendari city that is the object of research because its learning outcomes are still low, this is because only 64% of them meet the KKM. The purpose of this study: (1) describes the description of student learning activities taught through the application of probing learning models prompting class X IPS 3 MAN 1 Kendari on the material dynamics of the atmosphere and its effect on life (2) describing the description of teacher teaching activities through the application of probing learning models prompting class X IPS 3 MAN 1 Kendari in the matter of atmospheric dynamics and its effect on life (3) describing an increase in geography learning outcomes of class X IPS 3 MAN 1 Kendari taught through the application of probing learning models prompting the material dynamics of the atmosphere and its effect on life. The data in this study are qualitative and quantitative data obtained from observation sheets and learning outcomes tests. The results of the study showed that by applying the Probing Prompting learning model: (1) student learning activities increased with an average score of 3.4 in good category. (2) teacher teaching activities increased with an average score of 3.5 in good category. (3) the geography learning outcomes of students of Class X IPS 3 MAN 1 Kendari increased from an average score of 71 to an average score of 81, with learning completeness of 86.1% which was ≥ 75 according to the KKM determined by the school.MAN 1 Kendari adalah salah satu sekolah di kota Kendari yang menjadi objek penelitian karena hasil belajarnya yang masih rendah, hal ini dikarenakan hanya 64% yang memenuhi KKM. Tujuan penelitian ini :(1) mendeskripsikan gambaran aktivitas belajar siswa yang diajar melalui penerapan model pembelajaran probing prompting kelas X IPS 3 MAN 1 Kendari pada materi dinamika atmosfer dan pengaruhnya terhadap kehidupan (2) mendeskripsikan gambaran aktivitas mengajar guru melalui penerapan model pembelajaran probing prompting kelas X IPS 3 MAN 1 Kendari pada materi dinamika atmosfer dan pengaruhnya tehadap kehidupan (3) mengetahui gambaran peningkatan hasil belajar geografi siswa kelas X IPS 3 MAN 1 Kendari yang diajar melalui penerapan model pembelajaran probing prompting pada materi dinamika atmosfer dan pengaruhnya terhadap kehidupan. Data dalam penelitian ini adalah data kualitatif dan kuantitatif yang diperoleh dari lembar observasi dan tes hasil belajar. Hasil penelitian diperoleh bahwa dengan menerapkan model pembelajaran Probing Prompting: (1) aktivitas belajar siswa meningkat dengan skor rata-rata 3,4 berkategori baik. (2) aktivitas mengajar guru meningkat dengan skor rata-rata 3,5 berkategori baik. (3) hasil belajar geografi siswa Kelas X IPS 3 MAN 1 Kendari  meningkat dari rata-rata skor 71 menjadi rata-rata skor 81, dengan ketuntasan belajar 86,1% yang ≥ 75 sesuai dengan KKM yang ditentukan sekolah.